Where are the foundation phase teachers for our children? Black students’ perceptions - Steyn, MG; Harris , T; Hartell , CG (South African Journal of Higher Education, 2011)
The purpose of this research project was to explore how Black students perceive the reasons for the low enrolment of Black students in the Foundation Phase teacher education and training programmes at universities. Focus groups and follow up small group interviews were conducted to explore the reasons why Black students choose Foundation Phase and the factors that affected their experiences while enrolled in the programme. All interviews were recorded and transcribed and initially coded independently by each researcher. The codes were reviewed afterwards by all researchers as a team from which three main themes emerged from the interviewed data: (a) personal choices, (b) community influences and (c) institutional factors. Bronfenbrenner’s systems theory was used to conclude how students’ choices as well as environmental and institutional factors influence the enrolment of Black students in Foundation Phase teacher education and training programmes.